2017
DOI: 10.15537/smj.2017.2.18055
|View full text |Cite
|
Sign up to set email alerts
|

Hormone receptor status and survival of medullary breast cancer patients

Abstract: Objectives:To analyze the relationship between clinical features, hormonal receptor status, and survival in patients who were diagnosed with medullary breast cancer (MBC).Methods:Demographic characteristics, histopathological features, and survival statuses of 201 patients diagnosed with MBC between 1995 and 2015 were retrospectively recorded. Survival analyses were conducted with uni- and multivariate cox regression analysis.Results:Median follow-up time was 54 (4-272) months. Median patient age at the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 30 publications
(52 reference statements)
1
21
0
Order By: Relevance
“…In the present analysis the majority of patients (83%) were assessed as pN0 and the remaining 17% of patients were pN1. High lymph node involvement (pN3, pN4) has not been observed, which reflects positively on the overall survival (OS) and recurrence-free survival (RFS) time [12,[19][20][21]. The incidence of nodal metastasis is usually lower than in other BCs, especially IDC [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the present analysis the majority of patients (83%) were assessed as pN0 and the remaining 17% of patients were pN1. High lymph node involvement (pN3, pN4) has not been observed, which reflects positively on the overall survival (OS) and recurrence-free survival (RFS) time [12,[19][20][21]. The incidence of nodal metastasis is usually lower than in other BCs, especially IDC [21].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Aksoy et al. ( 8 ) found that patients with atypical MBC presented significantly superior rates of recurrence and RFS. This may be associated with a smaller number of selected cases, and these patients have less tumour growth and angiogenesis with fewer lymphocytes and mononuclear infiltration.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, HR status also affected the survival of MBC patients. Some studies found that MBC patients had a higher percentage of triple-negative status, and MBC patients with PR negativity exhibited good prognosis ( 8 , 9 ). However, the prognostic factors of AMCB were not mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, the prognosis of hormone receptor-negative patients is not very poor; several reports indicated that the prognosis of some patients with medullary cancer is relatively good, suggesting that it is related to the heterogeneity of the tumors. 4,5 TNBC is a subtype of breast cancer that lacks clinical therapeutic approaches due to the lack of corresponding therapeutic receptors and poor therapeutic efficacy of endocrine therapy and the molecular targeting of the drugs. 6,7 Studies have shown that TNBC is characterized by high proportion of young patients, high histological grade, high rate of axillary lymph node metastasis, low disease-free survival (DFS) and low overall survival (OS) compared with those in non-TNBC.…”
Section: Introductionmentioning
confidence: 99%
“… 3 However, the prognosis of hormone receptor-negative patients is not very poor; several reports indicated that the prognosis of some patients with medullary cancer is relatively good, suggesting that it is related to the heterogeneity of the tumors. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%